2011
DOI: 10.5539/elt.v4n1p79
|View full text |Cite
|
Sign up to set email alerts
|

Modal Auxiliary Verbs in Prescribed Malaysian English Textbooks

Abstract: The use of corpus-based findings in order to inform L2 teaching materials have been emphasized by many researchers owing to the fact that the studies of authentic texts have revealed some inconsistencies between the use of grammatical structures in corpora, and those found in language textbooks that are based purely on hunch. Therefore, by comparing a textbook corpus with the British National Corpus, this study attempts to shed light on the extent in which modal auxiliary verbs presented in the Malaysian presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…It was decided not to do a query for the other structures because according to Kennedy (2002, p. 89) these structures are "extremely rare". Another reason that we decided to eliminate these three structures from our list is that Mukundan and Khojasteh (2011) found that there is not even a single instance of these structures in their corpus-based analysis on Form 1, 2 and 3 Malaysian English language textbooks.…”
Section: Detailed Analysis Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It was decided not to do a query for the other structures because according to Kennedy (2002, p. 89) these structures are "extremely rare". Another reason that we decided to eliminate these three structures from our list is that Mukundan and Khojasteh (2011) found that there is not even a single instance of these structures in their corpus-based analysis on Form 1, 2 and 3 Malaysian English language textbooks.…”
Section: Detailed Analysis Of Datamentioning
confidence: 99%
“…To date, many studies questioned the authenticity of the language, grammar, pragmatics and vocabulary and phraseology presented in various national and international textbooks, and strongly noted that if learners were presented with appropriate grammatical structures in line with real language use, they would have encountered fewer difficulties handling relevant structures in communicative situations (Biber, Conrad, Reppen, Byrd and Helt, 2002;Gilmore, 2004;Meunier and Gouverneur, 2009;Romer, 2005Romer, , 2004aRomer, , 2004bNordberg, 2010, Mukundan andKhojasteh, 2011;Vellenga, 2004). Comparing the authenticity, grammar and vocabulary in textbooks and reference corpora such as Longman Spoken and Written English (LSWE) Corpus and British National Corpus (BNC), these studies indeed demonstrate that by ignoring frequent features of the language spoken or written by real language users, many textbooks implicitly portray these linguistic features as monolithic phenomena, which behave in the same way regardless of different contexts and situations of use.…”
Section: Introductionmentioning
confidence: 99%
“…Following similar approach as Romer's (2004a) in the comparative study of textbooks and BNC, Mukundan and Khojasteh (2011) reported that for certain modal auxiliaries, there was a mismatch between modal frequency order in lower secondary Malaysian English textbooks (Form 1-3) and the BNC. They also revealed that there were great differences in the relative frequency of verb phrase structures in which modals could occur.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard Malaysian ESL textbooks were not exceptions. The prescribed Malaysian English language textbooks used in schools are reportedly prepared through a process of material development that involves intuition and assumption (Mukundan, 2004;Mukundan & Roslim, 2009;Mukundan & Khojasteh, 2011). If such is the case, present-day textbooks might lack a broad empirical foundation which leads us to the first reason for carrying out such a study; because non-empirically based teaching materials can be positively misleading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation